Digital identity tokenization as a challenge to traditional legal concepts of property - Nodari, Gorgiladze (Український політико-правовий дискурс, 2025)
In the context of the spread of blockchain technologies and the emergence of the digital economy, a profound transformation of legal concepts related to property, personal data, and identity is underway. The tokenization of a person’s digital attributes creates a new paradigm of legal relations among the user, the state, and digital platforms, within which the line between private control and legal ownership becomes blurred. The relevance of the topic stems from the lack of a unified legal approach to identity tokens as objects of property rights and personal rights, which creates risks of legal uncertainty in the digital environment. The purpose of this article is to provide a theoretical and legal understanding of the phenomenon of tokenization of digital identity and to determine its impact on traditional concepts of property rights. The paper employs comparative legal, systemic, and structural, as well as analytical and formal legal methods. The comparative analysis covered the practices of the European Union, the United States, Ukraine, and Singapore. Empirical materials from eIDAS 2.0, GDPR, UCC-2022, and PDPA were used to identify standard and distinctive features. It was found that tokenization of digital identity combines elements of personal data, intellectual property, and digital assets, generating legal uncertainty regarding its status. In all the jurisdictions studied, the digital identity token is not recognized as an object of full ownership; instead, it is treated as a carrier of personal control rights. The concept of «digital ownership» is proposed – a new legal institution that allows the user to exercise control over the token without losing personal sovereignty. The need to harmonize technical standards (W3C VC 2.0, DID) with the legal frameworks of eIDAS 2.0 and national laws, as well as the creation of cross-border mechanisms for recognizing tokenized identifiers, is substantiated. The results obtained can be used to develop a national concept of digital identity for Ukraine, improve legislation in the field of electronic trust services and personal data protection, as well as contribute to the formation of international standards for digital ownership and cross-border legal cooperation in the field of digital identification.